How to Attract Quality FDI? - Theodore H. Moran; Holger Görg; Adnan Seric; Christiane Krieger-Boden (Kiel Centre for Globalization (KCG), 2017)
Foreign direct investment in developing countries has got a bad reputation in some popular discussions where it is set tantamount to first world's postcolonial exploitation of the raw materials and cheap labour from the third world, associated with pictures of leaking oil fields and collapsing factories. While this does happen, data show that FDI in developing countries increasingly flows to medium- to high-skilled manufacturing sectors rather than to resource-intensive and low-skilled sectors. And as skill levels needed by FDI increase, so do wage levels (ILO 2007, Coniglio et al. 2015). Accordingly, many emerging economies have built their success to a considerable degree on FDI flows to cover their enormous need for investments. The trick here is to attract "Quality FDI" that links foreign investors into the local host country economy. The current KCG Policy Paper provides evidence-based suggestions of how developing countries may attract Quality FDI successfully.
Keywords: 330